Systematic review of quality of life in persons with hereditary thoracic aortic aneurysm and dissection diagnoses. Issue 6 (2nd April 2019) - Velvin, Gry; Wilhelmsen, Jan E.; Johansen, Heidi; Bathen, Trine; Geirdal, Amy Ø.
Abstract : The purpose of this study was to explore the literature on quality of life (QoL) in patients with hereditary thoracic aortic aneurysm and dissection (HTAAD); including Marfan syndrome (MFS), Loeys‐Dietz syndrome (LDS), vascular Ehlers‐Danlos syndrome (vEDS) and other HTAAD diagnoses, critically appraising and synthesizing the relevant literature. A systematic review was performed by searching the published literature using available medical, physical, psychological, social databases and other sources. Studies addressing QoL in persons with an HTAAD diagnosis, published in peer‐reviewed journals were assessed. Of 227 search results, 20 articles satisfied the eligibility criteria. No studies of QoL in LDS, vEDS, or other HTAAD were found, only on MFS. Most studies had been published in the last 3 years. All were cross‐sectional quantitative studies besides one pilot intervention study. Most studies were of small sample size, had low response rate or participants without verified diagnosis. Despite these limitations, most studies indicate that having an HTAAD diagnosis as MFS may negatively impact QoL, but few studies found any associations between the biomedical symptoms and decreased QoL. More research is needed on QoL in samples with verified HTAAD diagnosis to develop evidence‐based knowledge and appropriate guidelines for these diagnoses. Abstract :